HUBUNGAN ANTARA KUALITAS LABA, ASIMETRI INFORMASI, DAN BIAYA MODAL EKUITAS: PENGUJIAN MENGGUNAKAN ANALISIS JALUR - Nasih, Moh.; Komalasari, Puput Tri; Madyan, Moh. (Jurnal Akuntansi dan Keuangan Indonesia, 2016)
This study examines the direct and indirect impacts of earnings quality on cost of equity capital by using path analysis. The quality of earnings is measured by two proxies, namely discretionary accrual and income smoothing. Information asymmetry is used as mediating variable. This study uses 3 years sample period, ie 2008-2010. This study finds that information asymmetry has two important roles in determining the cost of equity capital. Firstly, information asymmetry affects positively to cost of equity capital, and secondly, information asymmetries serve as mediator between earnings quality measured by discretionary accrual and the cost of equity capital. Nevertheless, there is no significant direct and indirect relationship between earnings quality and the cost of capital when earnings quality was measured by income smoothing.